FEASIBILITY STUDY ON THE USE OF THE TEN QUESTIONS SCREEN BY LADY HEALTH WORKERS TO DETECT DEVELOPMENTAL DISABILITIES IN PAKISTAN - Mirza, Ilyas; Mehmood, Tariq; Tareen, Amina; Davidson, Leslie; Rahman, Atif (Journal of Pakistan Psychiatric Society, 2008)
Objective: To assess the feasibility of using the Ten Question Screen (TQS) by Lady Health Workers to detect developmental disability. A secondary aim was to estimate the level of cognitive and learning disability within a well defined area in rural Pakistan.Design: Cross sectional survey.Place and duration of study: The study was conducted in Union Council Jatli, Subdistrict Gujar Khan, District Rawalpindi from January to April 2007.Subjects and Methods: We trained three lady health workers to administer Ten Questions Screen (TQS) within a well defined geographical area.Results: Out of 1789 children, 612 (34.2%) screened positive on TQS; 24.8 % screened positive on questions on mentally dull, backward or slow; sitting or walking delay; and reported inability to learn to do things like other children. 69.3% of those screened positive, belonged to 2 villages. The children of those 2 villages comprised 33% of total children screened.Conclusions: We found that primary health workers found TQS easy to use and were willing to incorporate its use in their routine practice. Future studies need to demonstrate the degree of health benefit associated with its use in primary care so that consideration can be given to its incorporation in a national screening programme. High positive screen in two villages may be due to genetic clustering and this requires further investigation.